Hybrid Models of Alternative Current Filter for Hvdc; MATEC Web of Conferences; Vol. 91 : Smart Grids 2017 - Ufa R. A. Ruslan Alexandrovich; Gusev A. S. Alexander Sergeevich; Vasilev A. S. Alexey Sergeevich; Lozinova N. G. Natalya (2017, 2017)
Title screen